Evolution of crystallographic phases in (Sr1-xCax)TiO3 with composition (x) - Ranjan R.; Pandey D.; Schuddinck W.; Richard O.; De Meulenaere P.; Van Landuyt J.; Van Tendeloo G. (My University, 2025)
Results of X-ray powder diffraction, neutron powder diffraction, electron microdiffraction, and convergent beam electron diffraction (CBED) studies are presented to show that the space group of (S1-xCax)TiO3 (SCT) in the composition range 0.35<x≤0.55 cannot be Cmcm. The correct space groups are Pbcm for 0.35<x ≤ 0.40 and Pbnm for 0.40< x ≤ 0.55. The analysis of powder XRD data reveals that the structure of SCT is noncubic for x ≥ 0.06. It is shown that four different types of orthorhombic phases appear in the SCT system with increasing Ca2+ content. © 2001 Academic Press.